Odpowiedzi

Najlepsza Odpowiedź!
2010-03-08T08:01:30+01:00
A)an=n²-9
n²-9=0
n²=9
n=3 lub n=-3
Odp Dla n równego 3 lub -3 wyrażenie n²-9 przyjmuje wartość 0.
B) a(n+1)=8(n+1)+3=8n+8+3=8n+11
an=8n+3
a(n+1)-an=8n+11-(8n+3)=8n+11-8n-3=8
Odp. Różnica tego ciągu wynosi 8.
2010-03-08T08:01:48+01:00
A) n²-9=0
n²=9
n=3 lub n=-3- odpada, bo n naturalne
Odp: n=3.

B) a_n+1=8(n+1)+3=8n+8+3=8n+11
a_n+1-a_n=8n+11-(8n+3)=8n+11-8n-3=8

Odp: r=8.
2010-03-08T08:03:46+01:00
A) an=n^{2}-9 an=0

0=n^{2}-9
n^{2}-9=0
n^{2}=9
n=3 u n=-3